The effect of training early childhood development practitioners on the principles of UDL to adapt lesson plans for children with communication impairments in the communication ELDA of the National Curriculum Framework - Samuels, Alecia (University of Pretoria, 2023)
Mini Dissertation (MA (Augmentative and Alternative Communication))--University of Pretoria, 2023.